2015
DOI: 10.1007/s10661-015-4371-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of Indonesian farmers regarding the use of personal protective equipment against pesticide exposure

Abstract: The use of synthetic pesticides in tropical countries has increased over the years, following the intensification of agriculture. However, awareness among farmers of the importance of protecting themselves from hazards associated with pesticide application is still lacking, especially in Indonesia. This paper reports results of an inventory on knowledge and attitudes regarding pesticide use by melon farmers of a village in Central Java, Indonesia. The importance of using personal protective equipment such as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 24 publications
9
50
0
2
Order By: Relevance
“…These findings were in conformity with that by Tamrin and Jamiluddin (2014) who reported that the knowledge score of pesticide management was high; however, the practice score, especially the use of personal protective equipment (PPE), was very poor 21) . In addition, the study by Yuantari et al (2015) suggested that almost none of the farmers used standardized PPE and used PPE completely 22) .Itmay be due to the high cost of PPE, hot tropical climatic conditions, poverty, or lack of training programs by the government 21,[23][24][25] . Some farmers had an inappropriate protective behavior, such as eating, drinking, smoking, taking a break, blowing or sucking a spray nozzle with their mouth, and spraying when it was windy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were in conformity with that by Tamrin and Jamiluddin (2014) who reported that the knowledge score of pesticide management was high; however, the practice score, especially the use of personal protective equipment (PPE), was very poor 21) . In addition, the study by Yuantari et al (2015) suggested that almost none of the farmers used standardized PPE and used PPE completely 22) .Itmay be due to the high cost of PPE, hot tropical climatic conditions, poverty, or lack of training programs by the government 21,[23][24][25] . Some farmers had an inappropriate protective behavior, such as eating, drinking, smoking, taking a break, blowing or sucking a spray nozzle with their mouth, and spraying when it was windy.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the threat of a nerve agent attack on the civilian population has remained largely theoretical, the broad use of the pesticides in agriculture leads to a large number of cases of pesticide poisoning [2] in the developing world. A lack of accurate reporting makes the data on the actual number of fatalities due to OPC toxicity difficult to determine, [3] but the World Health Organization (WHO) recognizes this as a significant problem that needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the findings of Fan et al [24], who highlighted that farmers get confused by the complexity of guidelines related to the proper use of pesticides; hence, they tend to misuse pesticides, reducing their protective behavior. Accordingly, the research related to the knowledge and attitudes on the use of pesticides needs to be further developed, focusing on farmers' practices [25]. In the agricultural field, several studies have investigated the safe behavior and risk perception of farmers.…”
mentioning
confidence: 99%